2019
DOI: 10.1016/j.injury.2019.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Unipolar versus bipolar hemiarthroplasty for displaced femoral neck fractures: A pooled analysis of 30,250 participants data

Abstract: Bipolar hemiarthroplasty is associated with greater range of motion and less acetabular erosion than unipolar hemiarthroplasty. 2  The operative time was longer during bipolar hemiarthroplasty compared to unipolar hemiarthroplasty.  No significant difference in hip function using Harris hip score, mortality, surgical, and medical outcomes is evident.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 50 publications
(85 reference statements)
0
2
0
2
Order By: Relevance
“…a bipolar ha may be advantageous in more functionally demanding patients due to less acetabular erosion and a lower revision rate compared to unipolar ha. [24][25][26] subgroup analyses in the most recent meta-analysis published before the health trial showed that the advantage for tha in reoperations was driven by comparison with unipolar ha. 6 this finding may be explained by the use of older, inferior ha implants.…”
Section: Discussionmentioning
confidence: 99%
“…a bipolar ha may be advantageous in more functionally demanding patients due to less acetabular erosion and a lower revision rate compared to unipolar ha. [24][25][26] subgroup analyses in the most recent meta-analysis published before the health trial showed that the advantage for tha in reoperations was driven by comparison with unipolar ha. 6 this finding may be explained by the use of older, inferior ha implants.…”
Section: Discussionmentioning
confidence: 99%
“…[6,12] Klinik çalışmalar ise bipolar protezler ile modüler unipolar protezlerin sonuçlarının benzer olduğunu göstermektedir. [23] Günümüzde, hemiartroplastinin ileri yaş, komorbid, düşkün ve fonksiyonel kapasitesi kısıtlı hastalarda uygulandığı düşünüldüğünde, maliyeti daha düşük olan unipolar başlar ile uygulamanın yeterli olacağı görülmektedir. [23] Son olarak, kalça kırıklı hastalarda diğer bir artroplasti alternatifi de 'dual mobil' veya 'tripolar' olarak isimlendirilen, TKA'nin asetabular yüzeyini, hemiartroplastinin de büyük, bipolar baş özelliğini beraberinde taşıyan eklemleşmelerdir.…”
Section: Hemiartroplasti Ve Total Kalça Artroplastisinde Cerrahi Yaklunclassified
“…[23] Günümüzde, hemiartroplastinin ileri yaş, komorbid, düşkün ve fonksiyonel kapasitesi kısıtlı hastalarda uygulandığı düşünüldüğünde, maliyeti daha düşük olan unipolar başlar ile uygulamanın yeterli olacağı görülmektedir. [23] Son olarak, kalça kırıklı hastalarda diğer bir artroplasti alternatifi de 'dual mobil' veya 'tripolar' olarak isimlendirilen, TKA'nin asetabular yüzeyini, hemiartroplastinin de büyük, bipolar baş özelliğini beraberinde taşıyan eklemleşmelerdir. Özellikle çıkık riskinin yüksek olduğu hastalarda TKA ve hemiartroplastiye iyi bir alternatif olarak düşünülmelidir.…”
Section: Hemiartroplasti Ve Total Kalça Artroplastisinde Cerrahi Yaklunclassified
“…Review studies have reported less pain, improved mobility, and long-term survivorship with cemented stems over uncemented stem prosthesis [ 4 ]. Further, a recent meta-analysis has also reported better range of motion, lower rates of acetabular erosion, and lower reoperation rates for bipolar prosthesis compared to the unipolar variant, but at the expense of longer operative time [ 5 ].…”
Section: Introductionmentioning
confidence: 99%